Structure and evolution of the horse zeta globin locus. - Flint, J; Taylor, A; Clegg, J (1988)
The equine zeta globin gene locus consists of an intact 5' gene and a truncated 3' pseudogene (psi zeta) that has only 5' control sequences and a first exon and intron. Nevertheless, the psi zeta gene has retained almost perfect homology with its neighbour, presumably by gene conversion. The first introns of both zeta and psi zeta genes contain a number of degenerate tandem repeats of a 14 base-pair sequence that has been found in the zeta genes of goats and humans and that is related to a family of human minisatellite sequences. Comparisons of sequences flanking the zeta and psi zeta genes reveal areas of considerable interspecies homology, which can be explained by a zeta gene duplication that pre-dated the mammalian radiation.